INFESTASI CAPLAK PADA TERNAK SAPI POTONG DI KANDANG PETERNAKAN SAPI KAMPUS II POLBANGTAN GOWA DI KABUPATEN BONE, PROVINSI SULAWESI SELATAN - Sri Wahyuni Ruslan; Sri Lestari (Cannarium, 2023)
In general, the obstacles experienced by breeders in efforts to increase livestock productivity include management or management of maintenance, fulfillment of feed nutrition, and safeguarding livestock health. One of the obstacles faced by cattle breeders is the emergence of parasitic agents that need to be overcome, namely ectoparasites. Ticks are one of the most common ectoparasites found in livestock and can reduce the quality and quantity of livestock products. Therefore, this study was conducted to determine the prevalence and preferences of tick infestation according to body part in beef cattle kept in Cattle Cages, Campus II Polbangtan Gowa, Bone Regency. This study used a purprosive sampling method, namely taking samples of adult beef cattle aged 2-7 years and over with an extensive and intensive rearing system. The number of beef cattle is 20 heads consisting of 7 males and 13 females. The collection of ticks was carried out manually using tweezers sequentially, starting from the head, neck, back, abdomen, groin of the forelegs, and groin of the hind legs. The identification of the type of tick found was Boophilus microplus, a species of tick from the sub-genus Boophilus with an infestation prevalence of 1.17% with the highest preference on the neck with an average of 44.9% individual ticks per cow in this study. Boophilus microplus ticks are a type of tick that is now commonly found in cattle and the way of maintenance greatly influences the infestation of Boophilus microplus ticks in cattle where the prevalence of tied cattle is greater than that of cows in pens.